PENGARUH INFLASI, KURS RUPIAH, LIKUIDITAS, DAN PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Intan Indah Cahyani (2023)
This study aims to analyze the effect of inflation, the rupiah exchange rate, liquidity, and profitability on the stock prices of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The purposive sampling method was used in this study by selecting 106 samples that met the criteria from a total population of 242 manufacturing companies listed on the IDX in the 2019-2022 period. The analysis technique used is panel data regression using Stata data processing software version 16. The results showed that inflation, the rupiah exchange rate, and liquidity (current ratio) did not have a significant effect on the stock prices of manufacturing companies listed on the IDX. However, profitability (ROE) has a significant effect on stock prices. That is, companies with higher levels of profitability tend to have higher stock prices. These results provide a deeper understanding of the factors that influence the stock prices of manufacturing companies on the IDX.